Pengaruh Latihan Interval Terhadap Kecepatan Lari 100 Meter Pada Siswa Kelas VIII SMP Budhi Luhur Kota Pekanbaru - Siti Hajar; Ramadi '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Based on my observation of student in class VIII SMP Budhi Luhur Kota Pekanbaru on atletics, they are not yet have no speed of run 100 metre. Especially in the rarely run 100 metre. This is due to the lack of a systematic workout, especially in strength training and adequate physical endurance. This is a challenge that needs to get attention from various circles, for which efforts need coaching achievements in athletics, especially in the rarely run. The purpose of this study was to determine the effect of interval training on the speed run 100 metre in class VIII SMP Budi Luhur Pekanbaru. As for who made the entire population in this study the research object, the eighth grade students of SMP Budi Luhur Pekanbaru City numbering 36 people. The sampling technique used is purposive sampling, ie sampling based on certain grounds. In this study the sample to be used is a male student for interval training will be much easier to implement if the sample is homogenous ie the male students only. Thus the number of samples in this study amounted to 11 people. The instruments used to collect data that pre-test and post test run 100 meters. The data obtained was analyzed using t-test. Based on the results of the t test results can be seen that t for 8.74> 1.833 (t-tables) and then the hypothesis is accepted, it means that there is a significant influence on the results of the exercise interval speed to run 100 meters in class VIII SMP Budi Luhur PekanbaruKeywords: interval training , the results of 100-meter sprint speed.1 Siti